Variation in melanin pigmentation of a sexually selected plumage trait and its adaptive value in the Common Snipe Gallinago gallinago. (6th October 2017) - Minias, Piotr; Surmacki, Adrian; Kudelska, Karolina; Podlaszczuk, Patrycja; Kamiński, Maciej; Kaczmarek, Krzysztof; Włodarczyk, Radosław; Janiszewski, Tomasz
Abstract : There is increasing evidence that melanin‐based plumage coloration correlates with different components of fitness and that it may act as a social or sexual signal of individual quality. We analysed variation in melanin pigmentation in the outermost tail feathers of the Common Snipe Gallinago gallinago . During courtship flights, male Snipe use their outermost tail feathers to generate a drumming sound, which plays a role in territory establishment and mate choice. As the outermost tail feathers are displayed to females during these flights, we predicted that conspicuous variation in their rusty‐brown (pheomelanin‐based) coloration may act as an honest signal of individual quality. To test this prediction, we spectrophotometrically measured brightness (an indicator of total melanin content) and red chroma (an indicator of pheomelanin content) of the outermost tail feathers in 180 juvenile and adult Common Snipe. An age‐related decline in feather brightness was found exclusively in females, suggesting that melanization could have evolved by natural selection to camouflage incubating birds. In both sexes, brightness of the tail feathers was inversely correlated with their structural quality (as measured with mass–length residuals), suggesting that melanization could increase mechanical properties of feathers and, in males, enhance the quality of courtship sonation. Red chroma positively correlated with total plasma protein concentration, supporting our prediction that pheomelanin pigmentation of tail feathers may act as an honest signal of condition. Our study indicated that variation in the melanin‐based coloration of the outermost tail feathers in the Common Snipe could have evolved as a result of several different selection pressures and it emphasizes the complexity of the processes that underlie the evolution of melanin‐based plumage coloration in birds.